1982
DOI: 10.1007/bf00442071
|View full text |Cite
|
Sign up to set email alerts
|

Gliadin- and immunoglobulin-containing cells of small intestinal lamina propria in childhood coeliac disease

Abstract: Abstract. One hundred twenty-five small intestinal biopsies of coeliac children and controls were investigated prospectively for gliadin binding by specific immunofluorescent staining of lamina propria cells, using a TRITC rabbit IgG antigliadinconjugate. In parallel, sera were investigated for serum gliadin antibodies by a red cell immunosorbent fluorescence test (RIFT). There was no epithelial or reticulin staining found with antigliadin. Exclusively in coeliac disease, i.e. in all active coeliacs, and in 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In a preliminary study of an untreated adult patient, we detected by indirect immunofluorescence staining of jejunal tissue sections a small fraction of PCs with specificity for gliadin peptides, and about 60% of these were of the IgA class [35]; interestingly, a much larger proportion of the total IgG than of the total IgA PC population was positive (5.7% versus 1.6%). Another preliminary immunofluorescence study based on intestinal specimens from children with coeliac disease indicated gliadin specificity in 11, 10.5, and 6.5% of the jejunal IgG + , IgM + , and IgA + PCs, respectively [44].…”
Section: Locally Produced Antibodies Dominated By the Homeostatic Igamentioning
confidence: 96%
“…In a preliminary study of an untreated adult patient, we detected by indirect immunofluorescence staining of jejunal tissue sections a small fraction of PCs with specificity for gliadin peptides, and about 60% of these were of the IgA class [35]; interestingly, a much larger proportion of the total IgG than of the total IgA PC population was positive (5.7% versus 1.6%). Another preliminary immunofluorescence study based on intestinal specimens from children with coeliac disease indicated gliadin specificity in 11, 10.5, and 6.5% of the jejunal IgG + , IgM + , and IgA + PCs, respectively [44].…”
Section: Locally Produced Antibodies Dominated By the Homeostatic Igamentioning
confidence: 96%
“…Gly coproteins from the mature villus zone showed only a very slight ability to bind glu ten, whereas binding was higher in the inter mediate zone between villous and crypt cells, and became maximal in the immature cryp tic cells [15]. Other investigators, however, were not able to demonstrate specific or pre ferred binding of gliadin to coeliac mucosal epithelium [17,18]. Further experiments are necessary to elucidate the mechanism of glia din action on the fetal intestine.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, a specific pattern of relative proportions of Ig-containing cells of lamina propria was found in CD and in CMPI. At least some of these reactions might be antigen-specific [42]. Changes in Ig-cell populations were shown to persist longer than histological damage in CD.…”
Section: Discussionmentioning
confidence: 99%
“…Incubations were done with working dilutions (1:100-1:10) of fluorescein isothiocyanate (FITC) -and tetramethyl rhodamine isothiocyanate (TRITC) -labelled antisera. Specificity of these conjugates has been tested by immunodiffusion, immunoelectrophoresis, and immunofluorescence using immunoglobulin-coupled human red cells [42].…”
Section: Immunofluorescent Histologymentioning
confidence: 99%